1989
DOI: 10.1530/jrf.0.0870063
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro development of zygotes from superovulated prepubertal and mature gilts

Abstract: Ten prepubertal and 8 mature gilts were superovulated with PMSG and hCG, and inseminated with fresh boar semen. Zygotes were surgically recovered from oviducts 54-60 h after hCG. One and 2-cell zygotes were randomly allotted to Medium PL (modified BMOC-3 supplemented with 0.1 mM-EDTA and 1.5% BSA) or Medium G (Medium PL without pyruvate or lactate). Eggs were washed twice in medium, and placed in microdrops of medium overlaid with silicon oil for culture in an humidified 5% CO2, 5% O2, 90% N2 environment, then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 15 publications
2
22
0
2
Order By: Relevance
“…In our experiment, the highest number and percentage of hatched embryos were obtained from gilts in the control group. Similarly, in the study of Pinkert et al [12], zygotes obtained from prepubertal gilts after induction of superovulation did not possess the same in vitro developmental potential as zygotes from pubertal gilts. Moreover, the authors observed that the development of embryos from prepubertal and mature gilts was similar to the morula but not the blastocyst stage.…”
Section: Discussionmentioning
confidence: 74%
“…In our experiment, the highest number and percentage of hatched embryos were obtained from gilts in the control group. Similarly, in the study of Pinkert et al [12], zygotes obtained from prepubertal gilts after induction of superovulation did not possess the same in vitro developmental potential as zygotes from pubertal gilts. Moreover, the authors observed that the development of embryos from prepubertal and mature gilts was similar to the morula but not the blastocyst stage.…”
Section: Discussionmentioning
confidence: 74%
“…Wiesak et al (1990) reported a dissimilar pattern of follicular development in PMSG-and hCG-treated, immature gilts compared with naturally cycling pigs. Also, porcine zygote development in vitro was greater when zygotes were collected from mature gilts than when they were collected from prepubertal gilts (Pinkert et al, 1989).…”
Section: Discussionmentioning
confidence: 91%
“…However, it has been found that immature oocytes from cows with reduced reproductive performance or slaughtered at the end of their use are heterogeneous in quality [9]. The developmental capacity of oocytes from pre-pubertal animals was lower than that of oocytes from adult animals (cattle: [14][15][16][17]; sheep: [18,19]; pig: [20]; goat: [21,22]). Follicular waves and advanced atresia of the ovary also affected the developmental competence of oocytes [11,23].…”
Section: Introductionmentioning
confidence: 99%